Dynamic Contract Breach - Fan Zhang (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2008)
This paper studies the design of optimal, privately-stipulated damages when breach of contract is possible at more than one point in time. It offers an intuitive explanation for why cancellation fees for some services (e.g., hotel reservations) increase as the time for performance approaches. If the seller makes investments over time to improve her value from trade, she will protect the value of her investments by demanding a higher compensation when the buyer breaches their contract at a time closer to when contract performance is due. Furthermore, it is shown that if the seller may be able to find an alternate buyer when breach occurs early but not when breach occurs late, the amount by which the damage for late breach exceeds the damage for early breach is increasing in the probability of finding an alternate buyer. (This result may explain why some hotels impose larger penalties for last-minute cancellations during the high season than during the low season.) When the probability of finding an alternate buyer is endogenized, the seller's private incentive to mitigate breach damages is shown to be socially insufficient whenever she does not have complete bargaining power with the alternate buyer. Finally, if renegotiation is possible after the arrival of each perfectly competitive entrant, the efficient breach and investment decisions are shown to be implementable with the same efficient expectation damages that implement the efficient outcomes absent renegotiation.
Keywords: D86; K12; 330; Contract; Breach